Pretreatment with Roxadustat (FG-4592) Attenuates Folic Acid-Induced Kidney Injury through Antiferroptosis via Akt/GSK-3β/Nrf2 Pathway. (20th January 2020) - Li, Xue; Zou, Yu; Xing, Jia; Fu, Yuan-Yuan; Wang, Kai-Yue; Wan, Peng-Zhi; Zhai, Xiao-Yue
Abstract : Folic acid- (FA-) induced kidney injury is characterized by the tubule damage due to the disturbance of the antioxidant system and subsequent interstitial fibrosis. FG-4592 is an inhibitor of prolyl hydroxylase of hypoxia-inducible factor (HIF), an antioxidant factor. The present study investigated the protective role of FG-4592 pretreatment at the early stage of the kidney injury and long-term impact on the progression of renal fibrosis. FG-4592 was administrated two days before FA injection in mice. On the second day after FA injection, the mice with FG-4592 pretreatment showed an improved renal function, compared with those without FG-4592 pretreatment, indicated by biochemical and histological parameters; meanwhile, the cellular content of iron, malondialdehyde, and 4-hydroxynonenal histologically decreased, implying the suppression of iron accumulation and lipid peroxidation. Simultaneously, upregulation of HIF-1 α was found, along with Nrf2 activation, which was reflected by increased nuclear translocation and high-expression of downstream proteins, including heme-oxygenase1, glutathione peroxidase4, and cystine/glutamate transporter, as well as ferroportin. Correspondingly, the elevated levels of antioxidative enzymes and glutathione, as well as reduced iron accumulation, were observed, suggesting a lower risk of occurrence of ferroptosis with FG-4592 pretreatment. This was confirmed by reversed pathological parameters and improved renal function in FA-treated mice with the administration of ferrostatin-1, a specific ferroptosis inhibitor. Furthermore, a signal pathway study indicated that Nrf2 activation was associated with increased phosphorylation of Akt and GSK-3 β, verified by the use of an inhibitor of the PI3K that phosphorylates Akt. Moreover, FG-4592 pretreatment also decreased macrophage infiltration and expression of inflammatory factors TNF- α and IL-1 β . On the 14 th day after FA injection, FG-4592 pretreatment decreased collagen deposition and expression of fibrosis biomarkers. These findings suggest that the protective role of FG-4592 pretreatment is achieved mainly by decreasing ferroptosis at the early stage of FA-induced kidney injury via Akt/GSK-3 β -mediated Nrf2 activation, which retards the fibrosis progression.